Failure Analysis of Centrifugal Pump Impeller in Textile Wastewater Using a Visual and Erosion-Corrosion Approach - Jejen Jaelani Frihatna; Wisnu Wijaya; Cecep Deni Mulyadi; Mohamad Agus Fhaizal; Winardi Sani; Hanny Rahayu (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2026)
Premature impeller failure is a major operational problem in textile wastewater treatment systems due to abrasive slurry flow and chemically aggressive environments. This study investigates the failure mechanism of a centrifugal pump impeller used in a textile wastewater treatment plant after approximately 1.5 years of operation. The impeller material was identified as gray cast iron operating under slurry wastewater conditions containing suspended abrasive particles and chemical contaminants. The failure analysis was conducted through visual inspection, morphology evaluation, and literature-based erosion–corrosion interpretation. Severe degradation was observed in the outer diameter region, including pitting, edge thinning, perforation, and material loss. The damage was associated with abrasive particle impact, high turbulence intensity, slurry flow, and corrosive wastewater exposure. The results indicate that synergistic erosion–corrosion was the dominant degradation mechanism. Erosion continuously removed the protective oxide layer, while corrosion accelerated material weakening and surface deterioration. Recent erosion studies on centrifugal pumps also reported severe degradation near blade tips and outer diameter regions due to high particle impact energy and turbulence effects. Compared with previous studies that separately discuss erosion or corrosion mechanisms, this study emphasizes the interaction of both mechanisms under textile wastewater operating conditions. The findings provide practical implications for improving pump reliability through better material selection, slurry filtration systems, and preventive maintenance strategies in wastewater treatment applications.